2020
DOI: 10.3897/pharmacia.67.e53886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of allergenicity of irradiated dairy products in a Balb/c mice model

Abstract: The objective of the present in vivo study was to analyze the changes in the immune response of the sensitized Ваlb/c mice against milk allergens in lyophilized cow’s milk (LCM) and whey curd (LC) before and after gamma irradiation (10 kGy). The results showed lower levels of IgE in the group treated with irradiated LCM (ICM) compared to the group treated with non-irradiated LCM (NiCM). Hence, it could be suggested that gamma irradiation influenced the epitopes of the major milk proteins and was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…No benefits were observed in the use of frog skin as a biological dressing on the healing of integumentary wounds produced in dogs [31], however, the authors did not use any method to alter the antigenicity of the xenograft, such as the gamma radiation used in the current study and by Adorno (2005) [11]. The use of gamma rays reduces antigenicity to food proteins and allergenicity [32].…”
Section: Discussionmentioning
confidence: 87%
“…No benefits were observed in the use of frog skin as a biological dressing on the healing of integumentary wounds produced in dogs [31], however, the authors did not use any method to alter the antigenicity of the xenograft, such as the gamma radiation used in the current study and by Adorno (2005) [11]. The use of gamma rays reduces antigenicity to food proteins and allergenicity [32].…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have indicated that ionizing radiation could reduce allergenicity by the destruction of human IgE-binding epitopes in milk allergens depending on the dose of irradiation [ 99 ]. A study assessing the allergenicity of irradiated dairy products in BALB/c mice revealed that gamma irradiation influenced the epitopes of the major milk proteins and was associated with lower allergenicity of lyophilized irradiated milk [ 100 ]. In line with this, another study, investigating ultrasound-assisted irradiation for reducing the allergenicity of β-lactoglobulin, revealed that IgE binding capacity and release of inflammatory mediators from human basophil cells were reduced significantly [ 69 ].…”
Section: Food Processing: Applied Techniques and Effect On The Allmentioning
confidence: 99%